Zircon fission-track dating of granites from the Vepor-Gemer Belt (Western Carpathians): constraints for the Early Alpine exhumation history - Plasienka,D.; Broska,I.; Kissova,D.; Dunkl,I. (Journal of Geosciences, 2007)
We present new zircon fission-track (ZFT) data from Variscan granitoid bodies in the Veporic (footwall unit) and Gemeric (hangingwall unit) thick-skinned nappe sheets of the Central Western Carpathians. All samples show Late Cretaceous to earliest Paleogene cooling ZFT ages, which contribute to constraining the low-temperature exhumation history of the Vepor-Gemer Belt. Four granite samples from the western part of the Gemericum near the contact with the underlying Veporicum provided central ZFT ages between 70.4 ± 5.4 and 74.7 ± 5.6 Ma. One sample from this area shows an older age of 87.7 ± 5.9 Ma, possibly owing to its higher structural position. One remoter sample from the SE part of the Gemeric Unit has 61.7 ± 3.4 Ma central ZFT age, which probably reflects exhumation associated with a younger compressional tectonic event in that area. One sample from the centre of the Veporic metamorphic core complex yielded a cooling age 64.9 ± 4.8 Ma. However, most of these samples exhibit an internal age scatter pointing to complex cooling and exhumation history influenced by a slow passage through the zircon partial annealing zone and/or reheating brought about by the Cretaceous Rochovce granite intrusion. In spite of this, the acquired ages generally match the exhumation trend of the Veporic metamorphic core complex.
Keywords: fission-track zircon data; exhumation; granites; Gemeric Unit; Veporic Unit; Western Carpathians